Persistent Activation of Innate Immunity in Patients with Primary Antibody Deficiencies - Gerasimina Tsinti; Demosthenes Makris; Anastasios E. Germenis; Matthaios Speletas (Journal of Immunology Research)
Primary antibody deficiencies (PAD) represent a heterogeneous group of disorders, with common variable immunodeficiency being the most common with clinical significance. The main phenotypic defect resides in the inability of B cells to produce antibodies, and the cornerstone of therapy is immunoglobulin replacement treatment in order to fight infections. However, the management of the other inflammatory manifestations is inadequate, reinforcing the hypothesis that a complex genetic background affecting additional cell populations, such as polymorphonuclear cells (PMN) and monocytes, influences the expression of the clinical phenotype of the disease. In this study, we investigated by flow cytometry in different conditions (resting state, and after isolation and incubation, with and without stimuli) the expression pattern of several markers on PMN and monocytes, indicative of their maturation, capacity for chemotaxis, adhesion, opsonization, migration, and phagocytosis in 25 PAD patients, 12 healthy blood donors, and 4 septic patients. In this context, we also analyzed patients before and after the initiation of replacement treatment, as well as an untreated patient in different clinical conditions. Interestingly, we observed that PAD patients exhibit a chronic activation status of the innate immunity compartment, along with several differences in the expression of activation, maturation, and adhesion markers, with respect to different clinical conditions. Moreover, immunoglobulin replacement treatment had a favorable effect on PMN, as it was expressed by a more mature and less activated phenotype on basal state cells, and an enhanced activation capacity after LPS exposure. Thus, we conclude that PAD patients display a persistent innate immune cell activation, which is probably associated with the chronic inflammatory stress, usually observed in these disorders.